Association between moderate-to-vigorous physical activity trajectories and academic achievement in Chinese primary school children: a 3-year longitudinal study - Junyu Wang; Yong Yang; Jun Wu; Ting Xie; Xuejun Guo; Xun Yuan; Ting Li; Yu Zhang; Huiying Zhao; Jie Zhuang (BMC Public Health)
Abstract Background Past cross-sectional studies have reported a positive association between moderate-to-vigorous physical activity (MVPA) and academic achievement in children and adolescents. Despite this, the influence of variations in MVPA over time on academic achievement remains yet to be definitively understood. Therefore, this study aims to track the patterns of MVPA and examine how they are associated with academic achievement over a three-year period among Chinese primary school students. Methods The longitudinal study examined the MVPA and academic achievement of a cohort of 202 primary school children over a three-year period. MVPA was assessed via accelerometers and analysed using Compositional Data Analysis (CoDA). Academic achievement was quantified using standardised test scores in reading, mathematics, and language. Group-Based Trajectory Models (GBTMs) were used to identify patterns of MVPA. Covariates such as demographics, sleep duration, and attitudes towards sports were adjusted in the Generalized Estimating Equations (GEEs) used to examine associations with academic achievement. All statistical analyses were conducted using R and SAS 9.4 software. Results This study identified three distinct MVPA trajectories: Low (74.8%), Decline (13.2%), and High (12.0%). At baseline, the High MVPA group had better academic achievement with mean scores of 89.8 in reading, 94.5 in mathematics, and 94.7 in language, compared to the Low MVPA group with mean scores of 80.4, 83.0, and 84.9, respectively. After adjustment for confounders, GEE models showed significant associations between MVPA trajectories and improved academic achievement. Compared to the Low MVPA group, the Decline MVPA group exhibited significant score increases in reading (β = 4.11, 95% CI: 1–7.21) and mathematics (β = 2.79, 95% CI: 0.09–5.5). The High MVPA group exhibited significant score increases in reading (β = 11.3, 95% CI: 7.93–14.67), mathematics (β = 12.32, 95% CI: 9.61–15.02), and language (β = 11.53, 95% CI: 8.99–14.06). Additionally, notable gender differences in MVPA trajectories were observed, and a positive association was found between favorable sports attitudes and improved academic achievement. Conclusions This study reveals three distinct MVPA trajectories among Chinese primary school children and demonstrates that those with high MVPA trajectories showcase superior academic achievements, particularly in reading, mathematics, and language. This highlights the vital role of MVPA in supporting academic excellence.